The value of brush cytology and biopsy for the diagnosis of colorectal cancer - Tatomirović Željka; Škuletić Vesna; Tufegdžić Ivana; Tomić Ljiljana; Džambas Jelena; Tarabar Dino (Vojnosanitetski Pregled)
Background/Aim. Although it is well-known the high sensitivity of brush cytology for the diagnosis of colorectal adenocarcinoma, this kind of diagnostics is not routinely used, and for the past years it has even been declining. The purpose of this study was to evaluate the value of brush cytology for the diagnosis of colorectal carcinoma, by comparison the results of brush cytology and biopsy, and then the results of both diagnostic methods with the final patohistological diagnosis of colorectal resection. Methods. This retrospective study included 173 patients with brush cytology of colorectal region during colonoscopy. In 166 patients concomitant biopsy specimens were obtained, and in 116 of them resection of the intestine as well. A total of the 106 patients underwent to all three diagnostic procedures. Results. Out of 166 patients who went through both brush cytology and biopsy, the congruent diagnosis was made in 129 (77.7%) patients: in 109 (65.7%) adenocarcinoma was diagnosed, which was confirmed after the resection of the intestine in 75 of the patients, and in 14 (8.4%) benign lesion, so there was no need for resection of the intestine. In 6 (3.6%) of the patients, both cytology and biopsy were negative, but the resected specimen was malignant. In 10 of the patients with malignant cytology in whom biopsy was not done, resection of the intestine confirmed malignancy. The sensitivity of detecting malignancy by brush cytology and biopsy were 87.9% and 78.3%, respectively (but this difference was not statistically significant, p = 0.083). Both methods had specificity and positive predictive values 100%. Negative predictive values for cytology and biopsy were 50% and 37.8%, respectively. The accuracy of cytology and biopsy was 89.2% and 80.8%, respectively. The combination of the results of brush cytology and biopsy increased the sensitivity of preoperative diagnostics to 94.8% which was significantly higher than sensitivity of biopsy (p < 0.001), but not than sensitivity of cytology (p = 0.102). Conclusion. Brush cytology could be a routine method, along with biopsy, in the diagnosis of colorectal malignancy. Both methods have comparable both sensitivity and accuracy, and its combination increases sensitivity of preoperative diagnostics of colorectal adenocarcinoma, which gives opportunity to better estimation of further diagnostic and therapeutic approach.